A controllable fabrication of grain boundary PbI2 nanoplates passivated lead halide perovskites for high performance solar cells. (August 2016) - Zhang, Taiyang; Guo, Nanjie; Li, Ge; Qian, Xufang; Zhao, Yixin
Abstract: We demonstrate a controllable formation of grain boundary PbI2 nanoplates passivated CH3 NH3 PbI3 and CH3 NH3 PbI2 Br perovskites for high performance solar cells with up to 17.8% and 14.4% efficiencies, which are higher than the corresponding phase pure perovskite solar cells. The PbI2 passivated planar perovskite films were facilely prepared via direct gas/solid reaction of hydrohalide deficient PbI2 ·xHI/Br precursor with CH3 NH2 gas. The amount of PbI2 impurities can be controlled by adjusting the hydrohalide deficiency in the precursors. The crystal growth investigation suggested that the PbI2 is highly like to form during the annealing crystallization process instead of existing in either the PbI2 ·xHI/Br precursor films or as grown perovskite films. The PbI2 with controllable amount locating at grain boundary could effectively passivate the perovskites with a longer PL lifetime and enhanced V oc . Graphical abstract: Highlights: The grain boundary PbI2 passivated CH3 NH3 PbI3 and CH3 NH3 PbI2 Br perovskites were facilely fabricated. The beneficial and side effect of PbI2 can be controlled by using hydrohalide deficient precursor of PbI2 ·xHX (X=I, Br). PbI2 passivated CH3 NH3 PbI2 Br perovskites exhibited 14.5% efficiency with 86% IPCE.